2002
DOI: 10.1016/s0092-8674(02)01133-9
|View full text |Cite
|
Sign up to set email alerts
|

ROS1, a Repressor of Transcriptional Gene Silencing in Arabidopsis, Encodes a DNA Glycosylase/Lyase

Abstract: Mutations in the Arabidopsis ROS1 locus cause transcriptional silencing of a transgene and a homologous endogenous gene. In the ros1 mutants, the promoter of the silenced loci is hypermethylated, which may be triggered by small RNAs produced from the transgene repeats. The transcriptional silencing in ros1 mutants can be released by the ddm1 mutation or the application of the DNA methylation inhibitor 5-aza-2'-deoxycytidine. ROS1 encodes an endonuclease III domain nuclear protein with bifunctional DNA glycosyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
725
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 665 publications
(748 citation statements)
references
References 41 publications
19
725
0
4
Order By: Relevance
“…Most of these genomic regions are in TEs or intergenic regions. Only a small number of genes are hypermethylated and silenced in Arabidopsis ros1 mutants, and the mutants do not show dramatic phenotypes in growth or development (7,14,19,21). Like ROS1 in Arabidopsis (20), SlDML2 in tomato preferentially targets highly methylated TEs and intergenic regions near genes (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Most of these genomic regions are in TEs or intergenic regions. Only a small number of genes are hypermethylated and silenced in Arabidopsis ros1 mutants, and the mutants do not show dramatic phenotypes in growth or development (7,14,19,21). Like ROS1 in Arabidopsis (20), SlDML2 in tomato preferentially targets highly methylated TEs and intergenic regions near genes (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…DNA methylation can be lost either because of failure in maintaining methylation after replication (i.e., passive DNA demethylation) or because of active removal by enzymes (i.e., active DNA demethylation). Previous studies have identified and characterized several enzymes important for active DNA demethylation in Arabidopsis (7)(8)(9)(10)(11). The ROS1 family of bifunctional 5-methylcytosine DNA glycosylases/lyases, often referred to as DNA demethylases, initiate active DNA demethylation by removing the methylcytosine base from the DNA backbone, resulting in a single nucleotide gap that can be filled with an unmethylated cytosine through a base excision repair pathway (7,8,12,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, studies have revealed that DME is expressed specifically in the central cell of the female gametophyte (Choi et al, 2002), leading to a tissue-specific removal of DNA methylation marks on the maternal genome and the establishment of genomic imprinting in Arabidopsis (Gehring et al, 2009). DNA glycosylases such as RE-PRESSOR OF SILENCING1 (ROS1), DEMETER-LIKE2 (DML2), and DML3 also are involved in the removal of 5-methylated cytosines in Arabidopsis (Gong et al, 2002), preventing the hypermethylation of specific genome regions (Penterman et al, 2007). Loss-of-function mutants of ROS1, DML2, and DML3 would result in significant changes of DNA methylation levels in all sequence contexts, particularly the CG dinucleotide in Arabidopsis (Penterman et al, 2007).…”
mentioning
confidence: 99%
“…The Arabidopsis genome encodes four DNA demethylases, including DEMETER (DME), REPRESSOR OF SILENCING 1 (ROS1)/DEMETER-LIKE 1 (DML1), DML2 and DML3. ROS1 is a major DNA demethylase that is involved in the dynamic transcriptional regulation of the genome (Gong et al 2002) that plays a role in the developmental processes and biotic and abiotic stress responses (Yamamuro et al 2014;Schumann et al 2017). DME is required for the expression of specific imprinted maternal alleles during seed development, while the biological function of DML2 and DML3 as yet remains mostly unknown (Bauer and Fischer 2011).…”
Section: Introductionmentioning
confidence: 99%